Use of questioning strategy to facilitate students’ reading comprehension in Taiwan - Ike Irawati (Journal on English as a Foreign Language, 2019)
This study investigates individual differences arising from strategy instruction, questioning strategy, based on the problems found through miscue analysis. This qualitative study also investigates students’ motivation toward the strategy taught. The participants were a college student in Taiwan, consisted of one high-achieving student and one low-achieving student. Both were on the same language proficiency level (level C). They were asked to complete miscue pre and post-test and took eight meetings of tutorials (four meetings for teacher-generated questions and four meetings for student-generated questions). An interview was also conducted to find out their motivation toward the strategy. The instructional materials were taken from an English magazine specially designed for Taiwanese, called Studio Classroom. Results indicated that the strategy did not work well in both students as their motivation interfered their reading performance. This study concludes that the strategy works better in higher motivation student. Since motivation affects students' reading performance, therefore, this study suggests that raising students' motivation in the teaching process is crucial to reach better reading performance.